UKMOD – A new tax-benefit model for the four nations of the UK - Matteo Richiardi; Diego Collado; Daria Popova (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2021)
In this paper, we introduce UKMOD, a new tax-benefit model for England, Wales, Scotland, Northern Ireland and the whole of the UK. The model originates and replaces as a stand-alone model the UK component of EUROMOD, the tax-benefit model for the European Union member states, which from 2021 is not updated anymore. We describe the main departures from EUROMOD, discuss some key assumptions including data issues, and provide information on the nowcasting and macro-validation procedure applied.
Keywords: 330; Microsimulation; Covid-19; Taxation; Welfare Benefits; Economics